Concepts for the development of multimedia für education - Wiemeyer, J. (International Journal of Computer Science in Sport, 2003)
Development of multimedia products should be a structured process, particularly when science is involved. In this contribution, the advantages and disadvantages of three different concepts for developing multimedia are discussed: - Software Engineering (SE) - New Media Engineering (NME) - Systematic Instructional Design (SID) The purpose of this contribution is to compare these three concepts concerning their viability and adaptability for developing multimedia products for educational goals. SE divides the development process into specific phases, e.g., planning, definition, sketch, implementation, introduction, and maintenance. NME comprises also six development phases: initialisation, basic concept, fine concept, realisation, introduction, and use. The first five phases result in a special milestone, respectively: disposition, treatment, multimedia script, test product, and final product. The main focus of SID is to take into consideration didactics, including didactics of media application and psychology of learning and cognition. SID comprises three main phases: analysis and planning, development and production, evaluation, revision, and using. These main phases are further divided into substeps. Each of the three concepts has specific strengths and weaknesses. Therefore, the best strategy is to combine the three concepts to ensure structure, specificity, transparency, and interdisciplinarity.